Integrated Approaches Revealed the Therapeutic Mechanisms of Zuojin Pill Against Gastric Mucosa Injury in a Rat Model with Chronic Atrophic Gastritis - Chen L; He T; Wang R; Liu H; Wang X; Li H; Jing M; Zhou X; Wei S; Zou W; Zhao Y (Dove Medical Press, 2024)
Lisheng Chen,1,2 Tingting He,3 Ruilin Wang,3 Honghong Liu,4 Xin Wang,1,2 Haotian Li,2 Manyi Jing,2 Xuelin Zhou,5 Shizhang Wei,6 Wenjun Zou,1 Yanling Zhao1,2 1College of Pharmacy, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 2Department of Pharmacy Department, The Fifth Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of China; 3Division of Integrative Medicine, The Fifth Medical Center of General Hospital of PLA, Beijing, People's Republic of China; 4Integrated TCM & Western Medicine Department, The Fifth Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of China; 5Department of Pharmacology, School of Basic Medical Sciences, Capital Medical University, Beijing, People's Republic of China; 6Department of Anatomy, Histology and Embryology, School of Basic Medical Sciences, Peking University, Beijing, People's Republic of ChinaCorrespondence: Yanling Zhao, Department of Pharmacy, The Fifth Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of China, Email zhaoyl2855@126.com Wenjun Zou, College of Pharmacy, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China, Email zouwenjun@163.comBackground: The Zuojin Pill (ZJP) is widely used for treating chronic atrophic gastritis (CAG) in clinical practice, effectively ameliorating symptoms such as vomiting, pain, and abdominal distension in patients. However, the underlying mechanisms of ZJP in treating CAG has not been fully elucidated.Purpose: This study aimed to clarify the characteristic function of ZJP in the treatment of CAG and its potential mechanism.Methods: The CAG model was established by alternant administrations of ammonia solution and sodium deoxycholate, as well as an irregular diet. Therapeutic effects of ZJP on body weight, serum biochemical indexes and general condition were analyzed. HE staining and AB-PAS staining were analyzed to characterize the mucosal injury and the thickness of gastric mucosa. Furthermore, network pharmacology and molecular docking were used to predict the regulatory mechanism and main active components of ZJP in CAG treatment. RT-PCR, immunohistochemistry, immunofluorescence and Western blotting were used to measure the expression levels of apoptosis-related proteins, gastric mucosal barrier-associated proteins and PI3K/Akt signaling pathway proteins.Results: The results demonstrated that ZJP significantly improved the general state of CAG rats, alleviated weight loss and gastric histological damage and reduced the serum biochemical indicators. Network pharmacology and molecular docking found that ZJP in treating CAG by inhibiting inflammation, suppressing apoptosis, and protecting the gastric mucosal barrier via the PI3K/Akt signaling pathway. Further experiments confirmed that ZJP obviously modulated the expression of key proteins involved in gastric mucosal cell apoptosis, such as Bax, Bad, Apaf-1, cleaved-caspase-3, cleaved-caspase-9, Cytochrome C, Bcl-2, and Bcl-xl. Moreover, ZJP significantly reversed the protein expression of Occludin, ZO-1, Claudin-4 and E-cadherin.Conclusion: Our study revealed that ZJP treats CAG by inhibiting the PI3K/Akt signaling pathway. This research provided a scientific basis for the rational use of ZJP in clinical practice.Keywords: Zuojin Pill, chronic atrophic gastritis, network pharmacology, molecular docking, PI3K/Akt signaling pathway